2009
DOI: 10.1007/s10832-009-9577-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of transport properties of interfacially controlled electroceramics: Application to n-conducting barium titanate

Abstract: Grain boundary regions in n-conducting barium titanate (BaTiO 3 ) are re-oxidized during the cooling process after sintering the ceramics in air. The kinetics of this reoxidation process is determined by rapid transport of oxygen along the grain boundaries and slow (rate-determining) diffusion of cation vacancies from the grain boundaries into the grains until the diffusion process is frozen-in. Based on numerical calculations of frozen-in diffusion profiles of cation vacancies at grain boundary regions for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Many authors have reported that GB resistivity is affected by the presence of surface acceptor states that originate from frozenin cation vacancies and act as conduction electron traps in the immediate vicinity of the grain boundary. 1,47,[54][55][56][57][58][59] Due to the repulsive Coulomb force, electrons are depleted in the near interface region giving rise to a positive space charge layer on either side of the GB core. The space charge layer is comprised of defects with positive effective charge whereas it is depleted of mobile negatively charged carriers.…”
Section: Section Ivc: Grain Boundary Conductivitymentioning
confidence: 99%
“…Many authors have reported that GB resistivity is affected by the presence of surface acceptor states that originate from frozenin cation vacancies and act as conduction electron traps in the immediate vicinity of the grain boundary. 1,47,[54][55][56][57][58][59] Due to the repulsive Coulomb force, electrons are depleted in the near interface region giving rise to a positive space charge layer on either side of the GB core. The space charge layer is comprised of defects with positive effective charge whereas it is depleted of mobile negatively charged carriers.…”
Section: Section Ivc: Grain Boundary Conductivitymentioning
confidence: 99%
“…This behaviour could be interpreted previously by means of an extended Schottky-barrier model. 23 Between 250 and 600 • C the activation energy corresponds to the Schottky-barrier height. In accordance with the Heywang model the PTC effect is accompanied by a rapid increase of the Schottky-barrier height at temperatures higher than the Curie-point.…”
Section: Ptc Behaviourmentioning
confidence: 99%
“…The validity of Eq. ( 14) well within the NTC regime and up to 900°C has been experimentally verified [31].…”
Section: ( )mentioning
confidence: 74%